Fourier cosine and sine transforms and generalized Lipschitz classes in the uniform metric - Volosivets, S.S.; Golubov, B.I. (Український математичний журнал, 2012)
For functions f ∈ L¹ (ℝ+) with cosine (sine) Fourier transforms f^c (f^s) in L¹ (ℝ), we give necessary and sufficient conditions in terms of f^c (f^s) for f to belong to generalized Lipschitz classes H^ω,m and h^ω,m Conditions for the uniform convergence of the Fourier integral and for the existence of the Schwartz derivative are also obtained. Для функцiй f∈L¹(R+) iз косинус-(синус-) перетвореннями Фур’є fˆc(fˆs) у L¹(R) наведено (в термiнах fˆc(fˆs) необхiднi та достатнi умови належностi функцiй f до узагальнених класiв Лiпшиця H^ω,m та h^ω,m. Також отримано умови рiвномiрної збiжностi iнтеграла Фур’є та iснування похiдної Шварца.